Auction design in strategic freight procurement - Marius Dellbrügge; Tim Brilka; Felix Kreuz; Uwe Clausen (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: This article aims to derive options for auction design in strategic freight procurement from the related literature and synthesize them into a design framework. Methodology: The proposed framework is based on a comprehensive literature review on auction design in strategic freight procurement. After conceptualizing the research topic and defining the scope of the review, a broad literature search was conducted. Inclusion and exclusion criteria were applied to select the literature. A coding scheme was used to extract the data. Findings: The literature review reveals design features and associated design options for each feature. This paper additionally identifies shortcomings in the scientific literature for auction design in strategic freight procurement. Based on this, the further need for research is derived. Originality: The literature to date has focused primarily on describing the auction process and solving the Winner Determination Problem as a subset of the auction process. In contrast, the specific auction design (e.g., bid types, lane design, number of auction rounds) is only considered in a fragmented way. The proposed framework fills this research gap by synthesizing design options from the freight procurement literature.
urn:nbn:de:gbv:830-882.0200880; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Innovation Management; Technology Management